Cellular Immune Responses and Hepatitis B Surface Antigen (HBsAg) in Alcohol-Consuming Fishermen : Respon Imun Seluler dan HBsAg pada Nelayan Pengonsumsi Alkohol - Nur Vita Purwaningsih; Tri Ade Saputro; Fitrotin Azizah; Ellies Tunjung Sari Maulidiyanti; Waras Budiman; Lukita Anggraini (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Hepatitis B infection remains a global health problem with long-term complications such as cirrhosis and hepatocellular carcinoma. Alcohol consumption is known to impair immune function and exacerbate hepatitis B virus (HBV) infection. Fishermen represent a high-risk occupational group due to alcohol consumption habits and limited healthcare access. This study aimed to analyze the relationship between alcohol consumption levels and hepatitis B infection status through HBsAg testing and lymphocyte count among fishermen. This was a descriptive observational study with a cross-sectional approach involving 40 fishermen in Gresik Regency. Data were collected through alcohol consumption questionnaires and laboratory tests, including HBsAg examination using a Rapid Test and lymphocyte count using a hematology analyzer. Data were analyzed using Chi-square and ANOVA tests with a significance level of p < 0.05. A total of 30% of respondents were HBsAg reactive, with the highest proportion found in the heavy alcohol consumption group (50%). The mean lymphocyte count decreased with increasing alcohol intake: 2.580 ± 420 cells/µL in the light group, 2.120 ± 390 cells/µL in the moderate group, and 1.780 ± 360 cells/µL in the heavy group (p = 0.012). There was a significant relationship between alcohol consumption level, HBsAg status, and lymphocyte count among fishermen. High alcohol consumption may reduce cellular immunity and increase the risk of persistent hepatitis B infection. HBsAg testing and lymphocyte count can serve as early indicators for health screening in high-risk occupational groups such as fishermen.